Assessment of Testicular Lhcgr mRNA Expression Correlated with Testis and Seminal Vesicle Activities in the Libyan jird (Meriones libycus, Rodentia: Muridae) during Breeding Season Compared with Nonbreeding Season - Radia Boufermes; Mansouria Belhocine; Zaina Amirat; Farida Khammar (Animals, 2021)
The Libyan jird (Meriones libycus, 1823) is a wild desert rodent that is a seasonal breeder species adapted to breed when the environmental conditions can satisfy the energy and hydrous requirements of pregnant and nursing females to ensure that births occur at the most favorable time of the year. We assessed gene expression of testicular luteinizing hormone receptor (Lhcgr) correlated to testis activity. The expression of Lhcgr was evaluated using quantitative Real Time-Polymerase Chain Reaction (qRT-PCR and the testis activity by a histological method in adult male Libyan jirds during the nonbreeding and breeding seasons. Our results showed that Lhcgr mRNA expression increased in autumn during the nonbreeding season and decreased in spring during the breeding season. This expression varied in contrast to testicular structure or function and plasma testosterone levels. These results help to elucidate this desert rodent’s seasonal sexual activity, which is correlated with central regulation.